O papel da escola normal secundária de São Carlos na constituição de um poder local de elite (1911-1923) - Jambersi, Belissa do Pinho (2014)
The research, based on the Sociology of Education, had, by goal, to understand the role played by the old Secondary Normal School of the city of São Carlos, in the constitution of a local leverage of intellectual elites characterized by a socially valued in the city lifestyle, during the period from 1911 to 1923. The research, through primary sources, rebuilt the relationships established between the school and the city, pointing out the symbolic elements of leverage / knowledge that determined the formation of the old Normal School, as a field of leverage propagated by cultural differences, disseminated within the daily relationships established in the city. As a category of analysis, was used the concepts of field, symbolic leverage, cultural capital, elite education and habitus from Education Sociology of Pierre Bourdieu, and also the concept of elite, according to authors like José Murilo de Carvalho.